2004
DOI: 10.1590/s0037-86822004000600002
|View full text |Cite
|
Sign up to set email alerts
|

Características clinicoepidemiológicas de um grupo de mulheres com HIV/AIDS em Salvador-Bahia

Abstract: The increasing number of HIV/AIDS infected women is one of the main characteristics of the AIDS epidemic, besides the wide expansion of the disease among the poor. This study focused on a group of 82 women with AIDS from Salvador-Bahia. The mean age was 32 +/- 7.2 years, 75% had children, 82.5% were jobless, and 77.8% were illiterate or only had basic education. The number of sexual partners was five or fewer in 71% of cases and 25% had only one sexual partner. Forty-six (55.4%) women reported up to 77 episode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
0
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
(6 reference statements)
4
0
0
3
Order By: Relevance
“…Seroprevalence in immunosuppressed individuals was similar to that reported by other studies in Brazil: Pará (82.9%) 13 and Bahia (77.3%) 23 .…”
Section: Discussionsupporting
confidence: 89%
“…Seroprevalence in immunosuppressed individuals was similar to that reported by other studies in Brazil: Pará (82.9%) 13 and Bahia (77.3%) 23 .…”
Section: Discussionsupporting
confidence: 89%
“…The rate between men and women was 2.5:1 (M:W), which is in agreement with the current trend of epidemic dissemination among women 24 . The low M:W rate obtained can be partially explained by sexual exposure as the most probable form of HIV transmission, with prominence of heterosexual behavior.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we found that HIV-positive pregnant and nonpregnant women from Northeast of Brazil had significantly lower education, income employment, and social status and higher number of children than those of women without HIV infection. These findings of impoverishment of the AIDS epidemic has been previously reported in others studies in Brazil [28][29][30][31] . In a study of HIV-infected women by Friedman et al, in 2011, an inverse correlation was observed between education level and pregnancy, and the risk of pregnancy was 75% higher among women with up to three years of education than that in women with nine years or more of education 29 .…”
Section: Discussionsupporting
confidence: 88%